Pengukuran Potensi Penerimaan Pajak PPh 21 Jasa Driver Online - Selvina Kobogau; Yustina Kowi; Daniel Duwiri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
There has been no measurement of potential income tax revenue 21, for taxpayers who are Gojek and Maxim driver partners in Jayapura City. So the purpose of the study, to measure the potential tax revenue of PPh 21 driver partners in Jayapura City. The research approach is quantitative, it is known that the research population is ± 981, the sampling method of variance data technique, the sample size is 203 respondents divided by 82 Gojek respondents and 121 Maxim respondents. Instruments and data collection methods, using a questionnaire there are 11 indicators with 30 statements. Data analysis methods through descriptive statistics: application of minimum, maximum, average, median, besides forming proportions to understand data contributions. Research findings, income PPh 21 Gojek driver partners amounted to IDR.132,140,600,-/year and Maxim IDR.206,459,200,-/year for the potential revenue of Jayapura City Government. The implication of the research is that the Jayapura City Government already has evidence of scientific findings of PPh 21 potential, there is a legal basis for taxation to state that driver partners are taxpayers. So that in the future the policy of extensification of Income PPh 21 will be carried out immediately, to support the contribution of taxes to PAD in Jayapura City.